Diversity of ants in citrus orchards and in a forest fragment in Southern Brazil - Golias, Halison Correia; Lopes, José; Delabie, Jacques Hubert Charles; de Azevedo, Fabio (EntomoBrasilis, 2018)
Abstract. The landscapes of the South and Southeast regions of Brazil are a mosaic of agroecosystems and vegetation in different stages of preservation, shapes and sizes and sizes and this changes the community structure of ants. Diversity of ants was compared in three different environments: orange orchard, lemon orchard and a forest fragment of the Brazilian Atlantic Forest biome, in the northwestern part of the State of Paraná, Brazil by a sampling method using pit-fall traps. Both richness and diversity of the species of ants were broader in the forest fragment than in the orchards; the fauna components were distributed rather homogeneously, as shown by the indices of equitability. The proximity of the areas sampled and the orchard management could be the main reasons to explain why all the species trapped in the experiments were found at least once in the forest remnant, whereas some groups of ants were not found in the orchards. Furthermore, the species of antes which were collected from the agricultural areas were mostly generalists and less diverse, leading to a monopoly of resources by a few, more prolific species. On the contrary, the ants living in forested areas were more diverse, where fewer individuals were found per species, and these were expected to be more specialized. The establishment of citrus orchards near the forest fragments may facilitate invasion by ants, especially the opportunistic species. Diversidade de formigas em pomares cítricos e em fragmento florestal no sul do Brasil Resumo. As paisagens das regiões Sul e Sudeste do Brasil são um mosaico de agroecossistemas e vegetação em diferentes estágios de preservação, formas e tamanhos e isso altera a estrutura da comunidade de formigas. A diversidade de formigas foi comparada em três ambientes diferentes: pomar de laranja, pomar de limão e fragmento florestal da Mata Atlântica brasileira, no noroeste do Estado do Paraná, por meio de um método de amostragem utilizando armadilhas de queda pitfall. Tanto a riqueza como a diversidade das espécies de formigas foram mais amplas no fragmento florestal do que nos pomares; Os componentes da fauna foram distribuídos de forma bastante homogênea, conforme demonstrado pelos índices de equitabilidade. A proximidade das áreas amostradas e a gestão do pomar podem ser as principais razões para explicar por que todas as espécies capturadas nos experimentos foram encontradas pelo menos uma vez no remanescente da floresta, enquanto que alguns grupos de formigas não foram encontrados nos pomares. Além disso, as espécies coletadas nos pomares eram na sua maioria generalistas e menos diversificadas, levando a um monopólio de recursos por algumas espécies mais prolíficas. Ao contrário, as formigas que viviam em áreas florestadas eram mais diversas, onde menos indivíduos eram encontrados por espécie, e esperava-se que fossem mais especializados. O estabelecimento de pomares de citros perto dos fragmentos florestais pode facilitar a invasão por formigas, especialmente as espécies oportunistas.